A methods engineering study on Albettie Leather Products - Bantola, Timothy; Galicia, Mary Jane.; Honrade, Lorrain Down. (Diliman, Quezon City College of Engineering, 2003)
Albettie Leather Products, a medium-scale manufacturing company that produces synthetic leather bags and belts, was studied. The study centered on methods improvement, and documentation and analysis is done through actual plant visits. Interviews with the workers and management, as well as observations of the work process, were conducted while employing various tools of Methods Engineering. Problem areas identified by the group as major problems are the absence of direct supervision and non-maximization of plant capacity. To solve these, they were looked at in detail and the factors that cause them were addressed. These were : no direct supervision, non-ergonomic work area, inefficient lay-out, undefined work schedule, many non-value adding operations. For each problem area, the group came up with at least two alternatives or solutions. A weighted criterion was formulated for each problem and every alternative was considered according to this criteria. The ones which scored the highest are deemed most desirable and are chosen. Upon determination of alternatives, the group computed for the potential benefits if these were implemented. The combined benefits amounted to a time savings of 15.49 minutes per unit of belt and 46.48 minutes per unit of a standard bag, mostly as a result of elimination of distance and travel time from assemblers to sewers, overlapping of rugby curing times and a more efficient operation. This translates to a potential increase in production by 699 belts and 337 bags per week, or an increment in revenue of P101,315.25 to P164,225.25 per week. An implementation plan and an implementation strategy are also proposed to serve as a guide for Albettie Leather Products so that they may be able to implement the various changes brought about by the alternatives. Hiring a foreman is the primary recommendation, for the effectiveness of the others hinge mainly on this. After this has been accomplished, the next step is the implementation of the work schedule and revised procedures. The last stage is to change the tables and the layout, preferably on the same non-working day.
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 32 : Methods Engineering
Keywords: Systems analysis